P112 X factor makeover for 4th year medical student lectures. (30th June 2016) - Boylan, Johnny; Forsyth, Sophie; Horner, Patrick
Abstract : Background/introduction: Traditionally Year 4 Medical students at Bristol University receive 4 hours of didactic lecture based teaching on sexual health topics. Overall, the feedback is satisfactory but student evaluations consistently denounce the volume of information contained in the lectures. Aim(s)/objectives: To support learner diversity and increase student participation, we decided to revamp the delivery of the sexual health curriculum. Methods: We made the lectures available on the student intranet for background reading and signposted the students towards additional sources of information such as BASHH guidelines. During a study day, 60 students in groups of 5 or 6 were asked to teach their peers using case studies on topics such as vaginal discharge, genital ulcers and sexual assault. Teaching methods included game shows, a rap about syphilis and role-play. There were prizes for the top three presentations (through peer grading) and a prize for the most innovative. A questionnaire, and open discussion were used to obtain feedback on both the old and new teaching formats. Results: Overwhelmingly the students preferred and gained more from the student led case based presentations. They felt more engaged and would recommend it for future groups. Some students felt it was also important to have an opportunity to ask questions about the online lectures in future. Discussion/conclusion: Through this alternative approach to learning new information, we have catered for different learning styles and created a positive learning environment. Peer teaching can be very effective in encouraging critical thinking and producing deeper learning outcomes.